Nawa Cita Jokowi-JK dalam Paradigma Pembangunan Ekonomi - Syamsi, Syam Surya (Surya University, 2015)
Nawacita are 9 (nine) main programs and the foundations of Indonesias development paradigm in the era of President Joko Widodo. Nawacita trying to get out of mainstream development paradigm since the New Order era to the post-reform which is the paradigm of growth. Development priorities not only about growth but also confirms the presence of state and government in society, expanding equitable development which reducing the waiver of public services. Another priority is to build economic independence and maintain cultural values through a mental revolution and the continuing restoration of the Nation. This research aims to interpret and analyze the Nawacita position in this line of thought emerging the development of paradigm in the global world and analyze potential bottlenecks in its operation activities. Research carried out by the analysis of literature through qualitative research methodology hermeneutics phenomenology. The results showed that Nawacita is sustainable and human development paradigm, but in its operation would face obstacles, especially from the bureaucratic apparatus and work culture..